Traditional rice storage facilities and options for safe storage: A study in some selected flood-prone areas under Bhola district (Journal of the Bangladesh Agricultural University, 2016)
The study aimed at identifying the existing rice storage facilities, problems and prospects at farmers level in some selected five unions in two flood-prone upazillas under Bhola district of Bangladesh. The farmers suggested policy options for safe storage of rice are also discussed. The selection of Upazilas and villages were done purposively whereas the sample households were selected randomly using stratified random sampling technique with arbitrary allocation. The farmers were classified as small, medium and large based their land ownership. Data on the average rice production, consumption, storage volume and costs of storage and losses of rice in different storage structures/containers from selected 50 farmers of study areas were collected through pre-tested questionnaire. The farmers generally used traditional storage structures such as Dole, Berh, Motka, Jala, Gola, Plastic drum and Gunny/Plastic bags for storing rice. Plastic drum, Gunny and Plastic bags and Motka/Jala were found more economical for the farmers considering the capital cost, expected life and storage loss. Over 90% of the farmers felt the need for training on safe storage and over 80% of the small and medium farmers were interested in getting government help through loans, grants, etc. About 60% of the farmers expressed their interest on cooperative storage system to store and protect their food grains during the time of floods. Farmers opined to construct storage structures at an easily accessible place within their village or union under common or cooperative storage systems. The proposed storage system, on implementation, could be managed or overseen by a committee elected/selected by the cooperative society members.J. Bangladesh Agril. Univ. 13(1): 125-130, June 2015